Advances in Colloid Science 2016
DOI: 10.5772/64898
|View full text |Cite
|
Sign up to set email alerts
|

Colloids: Applications in Sperm Preparation for Assisted Reproduction

Abstract: Colloids have been used for several decades to prepare spermatozoa for assisted reproduction, initially for in vitro fertilization but, with the development of scaled-up techniques, increasingly for artiicial insemination and cryopreservation as well. The colloids usually consist of coated silica particles. Using colloid centrifugation, it is possible to select sperm subpopulations consisting of motile spermatozoa with intact membranes, stable DN" and normal morphology and to separate them from the rest of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Therefore, the use of silane- and polyvinylpyrrolidone-coated colloid silica in density (DLC) and single (SLC) layer centrifugation protocols has revealed beneficial for selecting high quality spermatozoa [23–26], through the purification of high sperm number per analysis (i.e., up to 100 × 10 6 boar spermatozoa). However, the molecular mechanism of the SLC technique remains unclair [23], and its cost and low recovery yield may limit routine applications in swine farms [24, 27]. Recent studies have reported the use of conjugated magnetic nanoparticles as novel tools for molecular-based selection of spermatozoa regardless of the species [2830].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of silane- and polyvinylpyrrolidone-coated colloid silica in density (DLC) and single (SLC) layer centrifugation protocols has revealed beneficial for selecting high quality spermatozoa [23–26], through the purification of high sperm number per analysis (i.e., up to 100 × 10 6 boar spermatozoa). However, the molecular mechanism of the SLC technique remains unclair [23], and its cost and low recovery yield may limit routine applications in swine farms [24, 27]. Recent studies have reported the use of conjugated magnetic nanoparticles as novel tools for molecular-based selection of spermatozoa regardless of the species [2830].…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies were adopted to select the best spermatozoa within an ejaculate through targeted elimination of poor‐quality or damaged spermatozoa. Such techniques range from simple differential migration of spermatozoa, called the swim‐up assay (Chen et al, ; Mahadevan & Baker, ; Mortimer, ; Mortimer & Mortimer, ), to more complicated procedures based on density gradient centrifugation (e.g., albumin density (Ericsson, Langevin, & Nishino, ), or polyvinylpyrrolidone‐ and silane‐coated silica colloid solutions, such as Percoll™ and PureSperm®, respectively (Kaneko et al, ; Lessley & Garner, ; Morrell, )); filtration (glass wool (Paulson & Polakoski, ; Van der Ven et al, ), sephadex gel (Steeno, Adimoelja, & STEENO, ), or membrane (Agarwal, Manglona, & Loughlin, ); and microfluidic devices (Li et al, ; Shirota et al, ; Suarez & Wu, ). These purification procedures yield pure and high‐quality spermatozoa (motile and morphological normal) from both humans and animals, but the observed low and highly variable recovery efficiencies (10% to 63%), additional labor, and time‐consumption (>60 min) limit their utility to small‐scale applications (i.e., in vitro fertilization and intracytoplasmic sperm injection).…”
Section: Current Status Of Post‐collection Semen Handlingmentioning
confidence: 99%
“…The SLC permits the selection of highly motile and viable spermatozoa, with good chromatin integrity and better resistance to cryopreservation (Martinez‐Alborcia et al, , ). Furthermore, SLC is currently the most‐promising method for fast (∼30 min) purification of viable spermatozoa through species‐specific colloids (i.e., Androcoll™‐P for porcine and Androcoll™‐E for equine) (Morrell, ; Morrell & Wallgren, ). Yet, full integration of SLC in the swine breeding industry remains limited, likely due to its cost.…”
Section: Current Status Of Post‐collection Semen Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical procedures for sperm purification rely basically either on sedimentation or migration approaches to isolate fertile spermatozoa based on their density or motility (Singh et al., 2019). These include different density gradient filtration strategies (Morrell, 2016), swim‐up assay (Arias et al., 2017), single layer centrifugation (Nongbua et al., 2017) and Sephadex column filtration (Galarza et al., 2018). Moreover, taking the biochemical properties of abnormal spermatozoa into account, that is, lack of plasma membrane integrity and abnormal surface glycocalyx, has played an influential rule in developing these procedures even further (Odhiambo et al., 2011).…”
Section: Introductionmentioning
confidence: 99%